Building Organizational Culture Through Digitalization of Technology Service Post Management in Improving the Performance of Alamanda 28 Technology Service Post, Bojong Rawalumbu Sub District - Imansyah Abinda Firdaus; Agus Cholik; Muhammad Riksa Praba Haskara; Muhammad Ro'uuf Fadhillah; Ranty Purnamasari (Best Journal of Administration and Management, 2024)
This study analyzes organizational culture in the implementation of digitalization of the management of the Alamanda 28 Technology Service Post (Posyantek), Bojongrawalumbu Village, to improve public service performance. Using a qualitative approach with a case study method, data was collected through in-depth interviews, participant observation, and documentation studies. The research results show that digitalization has succeeded in increasing operational efficiency, transparency and accountability, as well as user satisfaction. This transformation is supported by transformational leadership, a culture of continuous learning, and collaboration between human resources. However, challenges such as resistance to change, infrastructure limitations, and digital literacy still need to be addressed. This study recommends prioritizing strengthening human resources, technology infrastructure, and developing a culture of innovation for the sustainability of digital transformation. This research provides theoretical and practical contributions to the management of technology-based public services at the sub-district level.